The Role of Leadership in Ruarl Head on Rural Finacial Management (A Case Study in Seretan Timu Rural Lembean Timur District Minahasa Regency) . - Manopo, Stefano Oktavian; Rumapea, Patar; Pangkey, Masje (Sam Ratulangi University, 2015)
ABSTRACT The success of the village government can run smooth and well because it is supported by many factors, one important factor is the village finances because it is impossible for the village to be able to carry out the village administration effective and efficient without adequate financial support. This is due to the financial capacity of the village depends on the size and variety of sources of income as financial resources are owned by the village. Therefore, the leadership of the village head and village, excavation and management of the financial resources of the village should be sought as optimal as possible to reach the village government administration efficient and effective as well as adhering to the Regulation of the Minister of Home Affairs Number 37 Year 2007 regarding the General Guidelines for Financial Management village. The aim of the research is to describe, analyze and find out how the village head's leadership role in the management of village finances (Case Study in the village of Seretan Timu drag troughs Minahasa District of East Lembean). This study used qualitative data analysis method presented descriptive with purposive sampling technique of sampling / sample aiming the number of informants there are fifteen informants. From the results of existing research, the village head's leadership role in the financial management of the village has not been complete worked well because there is no budget is unclear or data were incomplete, income and expenses can not be measured because it is not in accordance with the conditions of the village and village regulations only kinship systems but with all the shortcomings of existing good cooperation with the village officials to seek the implementation of the financial management of the village with transparancy, accountability and participation. Keywords: The Role of Leadership, Financial Management Rural